Method for producing hydrogen by coupling dicarboxylic acid prepared by electrocatalytic oxidation of cyclic alcohol / cyclic ketone
By doping transition metal layered hydroxide nanomaterials into the electrocatalyst, the problems of low current density and high oxygen byproducts in the electrocatalytic oxidation process were solved, realizing the preparation of highly efficient cyclic alcohol/cyclic ketone oxidation and hydrogen coupling products, thus improving energy utilization efficiency and environmental friendliness.
Patent Information
- Application Number
- CN202410577219.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-11-11
AI Technical Summary
The current density of existing electrocatalytic oxidation of cyclic ketones/cyclic alcohols to prepare dicarboxylic acids is low, a large amount of oxygen byproducts are generated, energy utilization efficiency is low, and traditional methods are highly corrosive to equipment, costly, and cause serious environmental pollution.
Transition metal-doped layered hydroxide nanomaterials were used as electrocatalysts. Transition metal hydroxide nano-electrocatalysts were prepared by co-precipitation and used for the electrocatalytic oxidation of cyclic alcohols/cyclic ketones. This process suppressed the oxygen evolution side reaction at the anode, improved energy utilization efficiency, and coupled hydrogen production at the cathode.
Achieving high Faradaic efficiency oxidation of cyclic alcohols/ketones at high current densities under room temperature and atmospheric pressure, suppressing anodic oxygen evolution side reactions, improving energy utilization efficiency, reducing nitrogen oxide emissions, and realizing the efficient preparation of dicarboxylic acids.
Smart Images

Figure CN120924994A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic organic matter conversion, specifically to a method for the electrocatalytic oxidation of cyclic alcohols / cyclic ketones to prepare dicarboxylic acids coupled with hydrogen production. Background Technology
[0002] Driven by rapidly rising energy demand and escalating environmental pollution, finding renewable energy sources to replace traditional oil, coal, and natural gas is imperative. Hydrogen energy is a recognized clean energy source with high energy density, and can be used to convert and store renewable energy sources (wind, hydro, and solar). However, traditional water electrolysis for hydrogen production suffers from drawbacks such as high reaction potential, high energy consumption, slow kinetics of the oxygen evolution reaction at the anode, and low oxygen value. Currently, using readily available renewable biomass resources to replace the oxygen evolution reaction at the anode through oxidation is a strategy to save energy and improve energy efficiency.
[0003] Dicarboxylic acids are an important class of industrial raw materials, mainly used as monomers for polymers. Adipic acid, in particular, is a crucial raw material for the synthesis of nylon and engineering plastics, with a global market value reaching $5 billion and continuing to grow. The traditional preparation process of adipic acid involves two steps: 1) using benzene, phenol, and cyclohexane as raw materials to prepare cyclohexanol and cyclohexanone; 2) oxidizing cyclohexanone / alcohol with concentrated nitric acid to adipic acid. This method is mature and produces high-purity products, but it requires highly corrosion-resistant equipment, consumes large amounts of nitric acid, is costly, and generates nitrogen oxide waste gas, causing environmental pollution. A greener process uses hydrogen peroxide instead of concentrated nitric acid as the oxidant, but this is not economically viable due to the excessively high oxidant content. With the increasing emphasis on environmental protection in my country, the development of new, green adipic acid production processes is becoming increasingly urgent.
[0004] Although recent literature has successfully prepared adipic acid via electrocatalysis of cyclohexanol / ketone using transition metal catalysts (Nat Commun 2022, 13(1), 5009; Angew. Chem. Int. Ed. 2022, 61(50), e202214977), the current density is difficult to meet the requirements of industrial production (>200 mA·cm). -2 Furthermore, increasing the current density generates a large amount of oxygen byproducts, which reduces energy utilization efficiency.
[0005] Therefore, how to increase the current density of electrocatalytic cyclic ketones / cyclic alcohols while reducing the occurrence of oxygen evolution side reactions is a technical problem that needs to be solved. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of low current density, large amount of oxygen byproducts, and low energy utilization efficiency in the electrocatalytic oxidation process of existing technologies. This invention provides a method for the electrocatalytic oxidation of cyclic alcohols / ketones to prepare dicarboxylic acids coupled with hydrogen production. This method involves doping a transition metal into a layered transition metal hydroxide to form a uniformly distributed layered transition metal hydroxide nanomaterial. Using this nanomaterial as the anode of the electrocatalyst enables the oxidation of cyclic alcohols / ketones with high Faradaic efficiency at high current density over a wide voltage range at room temperature and atmospheric pressure. This suppresses the oxygen evolution side reaction at the anode, improves energy utilization efficiency, and simultaneously produces hydrogen at the cathode without emitting nitrogen oxides.
[0007] To achieve the above objectives, the present invention provides a method for the electrocatalytic oxidation of cyclic alcohols / ketones to prepare dicarboxylic acids, wherein the method includes the following steps:
[0008] Using a transition metal hydroxide nano-electrocatalyst as the anode and a cathode catalyst as the cathode, an electrolyte solution containing cyclic alcohols and / or cyclic ketones was electrocatalyzed to obtain dicarboxylic acids.
[0009] The transition metal hydroxide nanoelectrocatalyst comprises transition metal hydroxide nanomaterials and a conductive substrate;
[0010] The transition metal hydroxide nanomaterial contains nickel and at least one of manganese, vanadium and copper.
[0011] Preferably, the preparation method of the transition metal hydroxide nano-electrocatalyst includes:
[0012] (1) Transition metal hydroxide nanomaterials were obtained by co-precipitation of transition metal salt solution and precipitant solution;
[0013] (2) The transition metal hydroxide nanomaterials are dispersed in an organic solvent and sprayed onto a conductive substrate to obtain a transition metal hydroxide nanoelectrocatalyst.
[0014] Preferably, the mass ratio of the nickel salt to the non-nickel transition metal salt is 4-30:1, more preferably 8-15:1.
[0015] The molar ratio of the transition metal salt in the transition metal salt solution to the precipitant in the precipitant solution is 1:1-4, preferably 1:1.2-2.
[0016] The beneficial effects achieved through the above technical solution are as follows:
[0017] In this invention, the method involves doping a transition metal into a layered transition metal hydroxide to form a uniformly distributed layered transition metal hydroxide nanomaterial. Using this nanomaterial as an electrocatalyst anode enables the oxidation of cyclic alcohols / ketones with high Faradaic efficiency at high current densities over a wide voltage range at room temperature and atmospheric pressure. This process suppresses the oxygen evolution side reaction at the anode, improves energy utilization efficiency, and produces hydrogen at the cathode without emitting nitrogen oxide waste gas. Attached Figure Description
[0018] Figure 1 This is a transmission electron microscope (TEM) image of the layered nickel-vanadium bimetallic hydroxide nanomaterial obtained in Example 1 of this invention.
[0019] Figure 2 This is a high-resolution transmission electron microscope image of the layered nickel-vanadium bimetallic hydroxide nanomaterial obtained in Example 1 of this invention;
[0020] Figure 3 This is a scanning electron microscope image of the layered nickel-vanadium bimetallic hydroxide nano-electrocatalyst obtained in Example 1 of this invention;
[0021] Figure 4 The linear sweep voltammetry curve of the layered nickel-vanadium bimetallic hydroxide nano-electrocatalyst obtained in Example 1 of this invention is shown.
[0022] Figure 5 This is a transmission electron microscope image of the layered nickel hydroxide nanomaterials obtained in Comparative Example 1 of this invention;
[0023] Figure 6 This is a high-resolution transmission electron microscope image of the layered nickel hydroxide nanomaterials obtained in Comparative Example 1 of this invention;
[0024] Figure 7 This is a scanning electron microscope image of the layered nickel hydroxide nano-electrocatalyst obtained in Comparative Example 1 of this invention;
[0025] Figure 8 These are the electrocatalytic oxidation results of the layered nickel-vanadium bimetallic hydroxide nano-electrocatalyst of Example 1 of the present invention under different voltages;
[0026] Figure 9 The results show the electrocatalytic oxidation of the layered nickel hydroxide nano-electrocatalyst of Comparative Example 1 of this invention under different voltages. Detailed Implementation
[0027] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0028] This invention provides a method for the electrocatalytic oxidation of cyclic alcohols / ketones to prepare dicarboxylic acids coupled with hydrogen production, wherein the method includes the following steps:
[0029] Using a transition metal hydroxide nano-electrocatalyst as the anode and a cathode catalyst as the cathode, an electrolyte solution containing cyclic alcohols and / or cyclic ketones was electrocatalyzed to obtain dicarboxylic acids.
[0030] The transition metal hydroxide nanoelectrocatalyst comprises transition metal hydroxide nanomaterials and a conductive substrate;
[0031] The transition metal hydroxide nanomaterial contains nickel and at least one of manganese, vanadium and copper.
[0032] In this invention, the method involves doping a transition metal into a layered transition metal hydroxide to form a uniformly distributed layered transition metal hydroxide nanomaterial. Using this nanomaterial as an electrocatalyst anode enables the oxidation of cyclic alcohols / ketones with high Faradaic efficiency at high current densities over a wide voltage range at room temperature and atmospheric pressure. This process suppresses the oxygen evolution side reaction at the anode, improves energy utilization efficiency, and produces hydrogen at the cathode without emitting nitrogen oxide waste gas.
[0033] In this invention, preferably, the transition metal elements of the transition metal hydroxide nanomaterial include nickel and vanadium.
[0034] According to the present invention, preferably, the preparation method of the transition metal hydroxide nano-electrocatalyst includes:
[0035] (1) Transition metal hydroxide nanomaterials were obtained by co-precipitation of transition metal salt solution and precipitant solution;
[0036] (2) The transition metal hydroxide nanomaterials are dispersed in an organic solvent and sprayed onto a conductive substrate to obtain a transition metal hydroxide nanoelectrocatalyst.
[0037] In this invention, a co-precipitation method is used to prepare transition metal hydroxide nano-electrocatalysts. The preparation method is simple. Through co-precipitation, the transition metal hydroxide nanomaterials in the transition metal hydroxide nano-electrocatalysts are uniformly distributed on the surface of the conductive substrate, increasing the number of active sites, improving electrocatalytic activity, and suppressing the occurrence of oxygen evolution side reaction at the anode.
[0038] According to the present invention, preferably, the co-precipitation conditions include: a co-precipitation temperature of 50-90℃, more preferably 60-85℃; and a co-precipitation time of 5-30 min, more preferably 10-15 min. In this invention, the method of controlling the co-precipitation temperature is not particularly limited; the co-precipitation temperature can be controlled to meet the above range using a constant-temperature water bath. Co-precipitation under the above conditions can rapidly prepare highly electrocatalyst-active transition metal hydroxide nano-electrocatalysts, and the co-precipitation conditions are mild.
[0039] In this invention, the equipment used for coprecipitation is not particularly limited, as long as it can perform the coprecipitation reaction.
[0040] According to a preferred embodiment of the present invention, the transition metal salt solution and the precipitant solution are simultaneously added to the coprecipitation apparatus. In this invention, the addition rate of the transition metal salt solution and the precipitant solution is not particularly limited; slow addition is sufficient to allow the coprecipitation reaction to proceed fully.
[0041] According to the present invention, preferably, the transition metal salt comprises a nickel salt and a non-nickel transition metal salt. In this invention, layered transition metal hydroxide nanocatalysts are obtained by co-precipitation of nickel and specific non-nickel transition metal elements. This enables intermetallic electronic interactions, enhances the adsorption of cyclic alcohols and / or cyclic ketones on the catalyst surface, and jointly achieves the preparation of high-performance, high-efficiency dicarboxylic acid compounds.
[0042] According to the present invention, preferably, the total mass concentration of transition metal salts in the transition metal salt solution is 5-50 g / L, for example, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, or any range between the two, preferably 10-30 g / L. In the present invention, the total mass concentration of transition metal salts refers to the sum of the mass concentrations of nickel salts and non-nickel transition metal salts.
[0043] According to the present invention, the type and source of the nickel salt are not particularly limited, and it is a conventional nickel salt in the art, which can be commercially available or prepared by existing technology. Preferably, the nickel salt is selected from at least one of nickel nitrate, nickel chloride, and nickel sulfate.
[0044] According to the present invention, the type and source of the non-nickel transition metal salt are not particularly limited. Preferably, the non-nickel transition metal salt is selected from at least one of vanadium salt, manganese salt, and copper salt. More preferably, the non-nickel transition metal salt is a vanadium salt, which utilizes the electronic interaction between nickel and vanadium elements in layered hydroxide nanomaterials to improve the adsorption capacity of cyclic alcohols / ketones on the catalyst surface, enabling the corresponding dicarboxylic acid products to be obtained with high Faradaic efficiency at high current densities, while greatly suppressing oxygen evolution side reactions, reducing bubble generation, and improving energy utilization efficiency.
[0045] According to the present invention, preferably, the non-nickel transition metal salt is selected from at least one of vanadium chloride, vanadium nitrate, vanadium oxysulfate, vanadium oxalate, manganese chloride, manganese sulfate, manganese nitrate, copper chloride, copper sulfate, and copper nitrate.
[0046] According to the present invention, preferably, the mass ratio of the nickel salt to the non-nickel transition metal salt is 4-30:1, for example, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 18:1, 20:1, 25:1, 30:1, or any range between the two, preferably 8-15:1. In the present invention, adding the nickel salt and the non-nickel transition metal salt according to the above mass ratio can effectively suppress the occurrence of the oxygen evolution side reaction under high current, achieving high-efficiency preparation of dicarboxylic acids while maintaining good stability.
[0047] According to the present invention, preferably, the molar ratio of the transition metal salt in the transition metal salt solution to the precipitant in the precipitant solution is 1:1-4, for example 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, or any range between the two, preferably 1:1.2-2.
[0048] According to the present invention, preferably, the mass concentration of the precipitant in the precipitant solution is 5-50 g / L, more preferably 14-30 g / L. The solvent of the precipitant solution is not particularly limited, but is preferably water.
[0049] According to the present invention, the precipitant is a precipitant conventionally used in coprecipitation reactions in the art. Preferably, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, potassium bicarbonate, urea, and ammonia. In the present invention, when the precipitant is ammonia, the mass concentration is expressed as NH3·H2O.
[0050] This invention also includes the steps of washing and drying the product of the coprecipitation reaction. The washing and drying are performed using conventional methods in the art. After centrifugation, washing, and drying, the product of the coprecipitation reaction is obtained as a layered transition metal hydroxide nanomaterial.
[0051] According to the present invention, those skilled in the art can select conventional conductive substrate materials. Preferably, the conductive substrate is selected from at least one of carbon cloth, carbon paper, nickel foam, nickel sheet, nickel mesh, copper foam, copper sheet, copper mesh, titanium sheet, titanium mesh, stainless steel sheet, stainless steel mesh, ITO conductive glass, and FTO conductive glass. More preferably, it is selected from at least one of nickel foam, nickel mesh, and carbon paper.
[0052] Preferably, this invention further includes a pretreatment step for the conductive substrate. The conductive substrate material is pretreated using conventional methods to remove surface oxides and organic impurities. According to a preferred embodiment of the invention, the conductive substrate material is washed with an acid solution, water, and acetone. Preferably, the washing is performed under ultrasonic conditions, and the washing time can be adjusted by those skilled in the art.
[0053] In this invention, preferably, the acid solution is a hydrochloric acid solution, and more preferably a hydrochloric acid solution with a mass concentration of 10-30 g / L.
[0054] In this invention, the organic solvent can be a conventional organic solvent in the art, preferably selected from at least one of methanol, ethanol, and acetone. The transition metal hydroxide nanomaterials are dispersed in the organic solvent and sprayed onto a conductive substrate to obtain a transition metal hydroxide nano-electrocatalyst. The layered transition metal hydroxide nanomaterials are uniformly dispersed on the surface of the conductive substrate material, obtaining more active sites. No additional calcination is required, avoiding the agglomeration of the transition metal hydroxide nanomaterials after calcination, which would affect the electrocatalytic activity.
[0055] In this invention, preferably, the mass of the sprayed transition metal hydroxide nanomaterial is 0.04-0.32g, for example, 0.04g, 0.06g, 0.08g, 0.1g, 0.12g, 0.14g, 0.16g, 0.18g, 0.2g, 0.24g, 0.28g, 0.32g, or any range between the two, preferably 0.08-0.16g, based on 1g of the mass of the conductive substrate.
[0056] In this invention, the spraying conditions are not particularly limited. Those skilled in the art can adjust the spraying conditions according to the adaptability of the conductive substrate material to uniformly spray the transition metal hydroxide nanomaterial onto the surface of the conductive substrate material.
[0057] According to the present invention, the cathode catalyst is made of a conventional electrode material in the art. The cathode catalyst material is selected from at least one of platinum, gold, silver, ruthenium, iridium, palladium, copper, and rhodium. The cathode catalyst is preferably a platinum sheet and / or a copper sheet.
[0058] According to the present invention, the cyclic alcohol can be a C3-C7 cyclic alcohol conventional in the art. Preferably, the cyclic alcohol is selected from at least one of cyclobutanol, cyclopentanol, and cyclohexanol. In the present invention, the mass concentration of the cyclic alcohol in the electrolyte solution containing the cyclic alcohol and / or cyclic ketone is not particularly limited, and those skilled in the art can adjust the mass concentration of the cyclic alcohol according to the conditions of the electrocatalytic oxidation reaction. Preferably, the mass concentration of the cyclic alcohol in the electrolyte solution containing the cyclic alcohol and / or cyclic ketone is 10-50 g / L, more preferably 30-40 g / L.
[0059] According to the present invention, the cyclic ketone can be a C3-C7 cyclic ketone conventional in the art. Preferably, the cyclic ketone is selected from at least one of cyclobutanone, cyclopentanone, and cyclohexanone. In the present invention, the mass concentration of the cyclic ketone in the electrolyte solution containing the cyclic alcohol and / or cyclic ketone is not particularly limited, and those skilled in the art can adaptively adjust the mass concentration of the cyclic ketone according to the conditions of the electrocatalytic oxidation reaction. Preferably, the mass concentration of the cyclic ketone in the electrolyte solution containing the cyclic alcohol and / or cyclic ketone is 10-50 g / L, more preferably 30-40 g / L.
[0060] According to the present invention, there is no particular limitation on the mass concentration of the electrolyte, as long as it can improve the conductivity of the solution. Preferably, the mass concentration of the electrolyte in the electrolyte solution containing cyclic alcohols and / or cyclic ketones is 10-100 g / L, more preferably 25-50 g / L.
[0061] According to the present invention, the electrolyte is a conventional compound that is soluble in aqueous solution or conducts electricity in the molten state.
[0062] According to the present invention, preferably, the electrolyte is selected from at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide and cesium hydroxide.
[0063] In this invention, the solvent for the electrolyte solution containing cyclic alcohols and / or cyclic ketones is a conventional solvent, preferably water.
[0064] According to the present invention, the electrocatalytic oxidation is carried out under conventional electrocatalytic oxidation conditions. Preferably, the conditions for the electrocatalytic oxidation include: an electrocatalytic voltage of 0.1-3V, for example 0.1V, 0.3V, 0.5V, 0.7V, 0.9V, 1V, 1.2V, 1.5V, 2V, 2.5V, 3V, or any range between the two, preferably 0.5-1.5V; and an electrocatalytic time of 1-24 hours, for example 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, or any range between the two, preferably 1-10 hours.
[0065] In this invention, the electrocatalytic oxidation is carried out at room temperature and atmospheric pressure. The transition metal hydroxide nano-electrocatalyst prepared by co-precipitation method can achieve high current density and high Faradaic efficiency oxidation of cyclic alcohols and / or cyclic ketones over a wide voltage range. Dicarboxylic acids are obtained at the anode, the occurrence of oxygen evolution side reaction at the anode is suppressed, and hydrogen production is coupled at the cathode, which has potential for industrial application.
[0066] In this invention, the electrode system for electrocatalytic oxidation is not particularly limited; a three-electrode system or a two-electrode system can be used. According to a preferred embodiment of the invention, the electrocatalytic oxidation of cyclic alcohols / ketones to prepare dicarboxylic acids is carried out in a three-electrode system. A transition metal hydroxide nanocatalyst is used as the anode, and a cathode catalyst is used as the cathode. The type of reference electrode is not particularly limited. Preferably, an Hg / HgO electrode and / or an Ag / AgCl electrode are used as the reference electrodes to construct the three-electrode system.
[0067] According to the present invention, the dicarboxylic acid is a product of the electrocatalytic oxidation of a cyclic alcohol and / or a cyclic ketone. Preferably, the dicarboxylic acid is selected from at least one of succinic acid, glutaric acid, adipic acid, and the corresponding lithium, sodium, and potassium salts of the three acids.
[0068] In this invention, the electrocatalytic oxidation products are quantitatively identified by liquid chromatography, and the Faraday efficiency and reaction rate are calculated.
[0069] According to a particularly preferred embodiment of the present invention, the method includes the following steps:
[0070] Using a transition metal hydroxide nano-electrocatalyst as the anode and a cathode catalyst as the cathode, an electrolyte solution containing cyclic alcohols and / or cyclic ketones was electrocatalyzed to obtain dicarboxylic acids.
[0071] The transition metal hydroxide nanoelectrocatalyst comprises transition metal hydroxide nanomaterials and a conductive substrate;
[0072] The transition metal hydroxide nanomaterial contains nickel and at least one of manganese, vanadium and copper as the transition metal element.
[0073] The preparation method of the transition metal hydroxide nano-electrocatalyst includes:
[0074] (1) Transition metal hydroxide nanomaterials were obtained by co-precipitation of transition metal salt solution and precipitant solution;
[0075] (2) The transition metal hydroxide nanomaterials are dispersed in an organic solvent and sprayed onto a conductive substrate to obtain a transition metal hydroxide nanoelectrocatalyst;
[0076] The transition metal salts include nickel salts and non-nickel transition metal salts;
[0077] The mass ratio of the nickel salt to the non-nickel transition metal salt is 8-15:1;
[0078] The molar ratio of the transition metal salt in the transition metal salt solution to the precipitant in the precipitant solution is 1:1.2-2;
[0079] The conditions for the electrocatalytic oxidation include: an electrocatalytic voltage of 0.5-1.5V and an electrocatalytic time of 1-10 hours.
[0080] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, all reagents used in the following examples and comparative examples are commercially available.
[0081] Preparation Example 1
[0082] (1) Prepare 20 mL of an aqueous solution containing 0.43 g nickel nitrate and 0.03 g vanadium chloride and 20 mL of a precipitant solution containing 0.56 g potassium hydroxide.
[0083] A transition metal salt solution and a precipitant solution were simultaneously added dropwise to a round-bottom flask under constant temperature water bath conditions of 80℃. The solution was added at a rate of 2 mL / min, and the reaction time was 10 minutes. The precipitate was then centrifuged, washed, and dried. Figure 1 The image shows a transmission electron microscope image of the obtained layered nickel-vanadium bimetallic hydroxide nanomaterial. Figure 1 As can be seen, the layered nickel-vanadium bimetallic hydroxide nanomaterials have a dispersed nanosheet structure. Figure 2 This is a high-magnification transmission electron microscope image of layered nickel-vanadium bimetallic hydroxide nanomaterials, from... Figure 2 As can be seen, nanomaterials have the structural characteristics of ultrathin nanosheets.
[0084] (2) The nickel foam was ultrasonically washed for 10 minutes each with 20 g / L hydrochloric acid solution, deionized water, and analytical grade acetone to remove surface oxides and organic impurities, and then dried. 0.02 g of the obtained layered nickel-vanadium bimetallic hydroxide nanomaterial was dispersed in ethanol and sprayed onto 0.25 g of the nickel foam substrate to obtain the layered nickel-vanadium bimetallic hydroxide nano-electrocatalyst, denoted as S1. Figure 3 Scanning electron microscope (SEM) image of layered nickel-vanadium bimetallic hydroxide nanocatalyst, from Figure 3 As can be seen, nickel-vanadium bimetallic hydroxide nanomaterials were successfully coated on a nickel foam conductive substrate.
[0085] Preparation Example 2
[0086] Following the method of Preparation Example 1, except that 0.01 g of vanadium chloride was used instead of 0.03 g of vanadium chloride, and the other conditions were the same as in Preparation Example 1, a layered nickel-vanadium bimetallic hydroxide nano-electrocatalyst was obtained, denoted as S2.
[0087] Preparation Example 3
[0088] Following the method of Preparation Example 1, except that 0.12 g of vanadium chloride was used instead of 0.03 g of vanadium chloride, and the other conditions were the same as in Preparation Example 1, the resulting layered nickel-vanadium bimetallic hydroxide nano-electrocatalyst was denoted as S3.
[0089] Preparation of Comparative Example 1
[0090] (1) Prepare 20 mL of an aqueous solution containing 0.43 g of nickel nitrate and 20 mL of a precipitant solution containing 0.28 g of potassium hydroxide. Simultaneously add the transition metal salt solution and the precipitant solution to a round-bottom flask under constant temperature water bath conditions at 80 °C. The reaction is completed within 10 minutes. After centrifugation, washing, and drying, Figure 5 The image shows a transmission electron microscope (TEM) image of the obtained layered nickel hydroxide nanomaterials. Figure 6 To obtain high-resolution transmission electron microscopy images of the obtained layered nickel hydroxide nanomaterials, from Figure 5 and Figure 6 It can be seen from this that nanomaterials also have the characteristics of ultrathin nanosheets.
[0091] (2) The nickel foam was ultrasonically washed for 10 minutes each with 20 g / L hydrochloric acid solution, deionized water, and analytical grade acetone to remove surface oxides and organic impurities, and then dried. 0.02 g of the obtained layered nickel hydroxide electrocatalyst was dispersed in ethanol and sprayed onto 0.25 g of the nickel foam substrate to obtain the layered nickel hydroxide nano-electrocatalyst, denoted as D1. Figure 7 To obtain scanning electron microscope (SEM) images of layered nickel hydroxide nanocatalysts, from Figure 7 As can be seen, layered nickel hydroxide nanomaterials were successfully coated onto the nickel foam conductive substrate.
[0092] Preparation of Comparative Example 2
[0093] Following the method of Preparation Example 1, except that vanadium chloride was replaced with an equal amount of ferric chloride, and other conditions were the same as in Preparation Example 1, a layered nickel-iron bimetallic hydroxide nano-electrocatalyst was obtained, denoted as D2.
[0094] Preparation of Comparative Example 3
[0095] The method of Example 1 was followed, except that 0.08 g of chromium nitrate nonahydrate was used instead of 0.03 g of vanadium chloride for preparation, resulting in a layered nickel-chromium bimetallic hydroxide nano-electrocatalyst denoted as D3.
[0096] Example 1
[0097] A 20 mL aqueous solution containing 0.8 g of cyclohexanone and 0.56 g of potassium hydroxide was prepared as the electrolyte solution. A three-electrode system was constructed using the S1 electrocatalyst as the anode, a platinum sheet as the cathode, and an Hg / HgO electrode as the reference electrode. The reaction was continuously stirred for 1 hour at a constant voltage of 0.9 V relative to the Hg / HgO electrode (equivalent to 1.8 V relative to the reversible hydrogen electrode). A sample was then added to a 1:1 volume ratio of dilute sulfuric acid solution (1 mol / L), and adipic acid was quantitatively identified using liquid chromatography. The results are shown in Table 1.
[0098] Figure 4 The linear sweep voltammetry curves of the layered nickel-vanadium bimetallic hydroxide nanocatalyst obtained in Example 1 are shown below. Figure 4 It can be seen that the nickel-vanadium bimetallic hydroxide nanocatalyst has high electro-oxidation activity of cyclohexanone.
[0099] Example 2
[0100] A 20 mL solution containing 0.8 g of cyclohexanone and 1.12 g of potassium hydroxide was prepared as the electrolyte solution. A three-electrode system was constructed using the S1 electrocatalyst as the anode, a platinum sheet as the cathode, and an Hg / HgO electrode as the reference electrode. Compared to Example 1, the voltage relative to the reversible hydrogen electrode was kept constant at 1.8 V. Based on the change in potassium hydroxide concentration, the voltage relative to the Hg / HgO electrode was corrected to 0.87 V. The reaction was continuously stirred at a constant voltage of 0.87 V for 1 hour. A sample was taken and added to a dilute sulfuric acid solution (1 mol / L) at a volume ratio of 1:1. Adipic acid was quantitatively identified using liquid chromatography. The results are shown in Table 1.
[0101] Example 3
[0102] A 20 mL solution containing 0.8 g of cyclohexanone and 1.68 g of potassium hydroxide was prepared as the electrolyte. A three-electrode system was constructed using the S1 electrocatalyst as the anode, a platinum sheet as the cathode, and an Hg / HgO electrode as the reference electrode. Compared to Example 1, the voltage relative to the reversible hydrogen electrode was kept constant at 1.8 V. Based on the change in potassium hydroxide concentration, the voltage relative to the Hg / HgO electrode was corrected to 0.86 V. The reaction was continuously stirred at a constant voltage of 0.86 V for 1 hour. A sample was added to a dilute sulfuric acid solution (1 mol / L) at a volume ratio of 1:1, and adipic acid was quantitatively identified using liquid chromatography. The results are shown in Table 1.
[0103] Example 4
[0104] Electrocatalytic oxidation was performed according to the method in Example 1, except that the transition metal hydroxide nanocatalyst at the anode was S2, and the results are shown in Table 1.
[0105] Example 5
[0106] Electrocatalytic oxidation was performed according to the method in Example 1, except that the transition metal hydroxide nanocatalyst at the anode was S3, and the results are shown in Table 1.
[0107] Example 6
[0108] A 20 mL solution containing 0.204 g of cyclohexanol and 0.8 g of sodium hydroxide was prepared as the electrolyte solution. A three-electrode system was constructed using the S1 electrocatalyst as the anode, a platinum sheet as the cathode, and an Hg / HgO electrode as the reference electrode. Compared to Example 1, the voltage relative to the reversible hydrogen electrode was kept constant at 1.8 V. Based on the change in sodium hydroxide concentration, the voltage relative to the Hg / HgO electrode was corrected to 0.87 V. The reaction was continuously stirred at a constant voltage of 0.87 V for 4 hours. A sample was taken and added to a dilute sulfuric acid solution (1 mol / L) at a volume ratio of 1:1. Adipic acid was quantitatively identified using liquid chromatography. The results are shown in Table 1.
[0109] Comparative Example 1
[0110] A 20 mL solution containing 0.8 g of cyclohexanone and 0.56 g of potassium hydroxide was prepared as the electrolyte. A three-electrode system was constructed, using D1 electrocatalyst as the anode, a platinum sheet as the cathode, and an Hg / HgO electrode as the reference electrode. The reaction was continuously stirred at a constant voltage of 0.9 V for 1 hour. A sample was taken and added to a 1:1 volume ratio of dilute sulfuric acid solution (1 mol / L). Adipic acid was quantitatively identified using liquid chromatography, and the results are shown in Table 1.
[0111] Comparative Example 2
[0112] Electrocatalytic oxidation was performed according to the method in Example 1, except that the transition metal hydroxide nanocatalyst at the anode was D2, and the results are shown in Table 1.
[0113] Comparative Example 3
[0114] Electrocatalytic oxidation was performed according to the method in Example 1, except that the transition metal hydroxide nanocatalyst at the anode was D3, and the results are shown in Table 1.
[0115] Comparative Example 4
[0116] Electrocatalytic oxidation was performed according to the method in Example 6, except that the transition metal hydroxide nanocatalyst at the anode was D1, and the results are shown in Table 1.
[0117] Test Example 1
[0118] The results of the electrocatalytic oxidation of cyclohexanone to prepare adipic acid in the examples and comparative examples are shown in Table 1.
[0119] Adipic acid Faraday efficiency = (Number of electrons consumed in the actual molar amount of adipic acid produced / Total number of electrons consumed in the reaction) × 100%; the adipic acid Faraday efficiency is taken as the optimal value of the test results;
[0120] Oxygen Faraday efficiency = (Number of electrons consumed by the actual molar amount of oxygen produced / Total number of electrons consumed in the reaction) × 100%; Oxygen Faraday efficiency and adipic acid Faraday efficiency are derived from the same test;
[0121] Adipic acid formation rate = the mass of adipic acid produced per hour on a catalyst per square centimeter geometric area.
[0122] Table 1
[0123]
[0124] As shown in Table 1, the layered hydroxide nano-electrocatalyst prepared using the examples of this invention exhibits higher Faradaic efficiency and a faster formation rate when used for the electrocatalytic oxidation of cyclohexanone and cyclohexanol to adipic acid, while also showing fewer anodic oxygen evolution side reactions. The adipic acid formation rate is affected by both Faradaic efficiency and current density. The ratio of nickel salt to vanadium salt is crucial; an excessively high nickel-to-vanadium salt mass ratio reduces the Faradaic efficiency of adipic acid, thus decreasing the formation rate, while an excessively low ratio reduces the current density during the electrocatalytic oxidation process, further decreasing the formation rate.
[0125] Test Example 2
[0126] A 20 mL solution containing 0.8 g of cyclohexanone and 0.56 g of potassium hydroxide was prepared as the electrolyte solution. A three-electrode system was constructed using an S1 electrocatalyst as the anode, a platinum sheet as the cathode, and an Hg / HgO electrode as the reference electrode. The reaction was continuously stirred for 1 hour at constant voltages of 0.6 V, 0.7 V, 0.8 V, 0.9 V, and 1.0 V, respectively. Samples were taken and diluted with 1 mol / L dilute sulfuric acid solution at a 1:1 volume ratio. Adipic acid was quantitatively identified using liquid chromatography, and the average value of the results was plotted. Figure 8 .
[0127] Using the same three-electrode system, but replacing the anode with D1 electrocatalyst, the reaction was continuously stirred for 1 hour at constant voltages of 0.6V, 0.7V, 0.8V, 0.9V, and 1.0V, respectively. Adipic acid was quantitatively identified using liquid chromatography, and the average value of the results was plotted. Figure 9 .
[0128] from Figure 8 and Figure 9As can be seen, the electrocatalyst of Preparation Example 1 can maintain a low oxygen content at the anode when electrocatalytic oxidation is carried out at a higher voltage. However, the electrocatalyst of Comparative Example 1 shows that the oxygen content of the byproduct increases significantly after the voltage of electrocatalytic oxidation is increased, and the side reaction is difficult to suppress.
[0129] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing dicarboxylic acids by electrocatalytic oxidation of cyclic alcohols / ketones, characterized in that, The method includes the following steps: Using a transition metal hydroxide nano-electrocatalyst as the anode and a cathode catalyst as the cathode, an electrolyte solution containing cyclic alcohols and / or cyclic ketones was electrocatalyzed to obtain dicarboxylic acids. The transition metal hydroxide nanoelectrocatalyst comprises transition metal hydroxide nanomaterials and a conductive substrate; The transition metal hydroxide nanomaterial contains nickel and at least one of manganese, vanadium and copper.
2. The method according to claim 1, wherein, The preparation method of the transition metal hydroxide nano-electrocatalyst includes: (1) Transition metal hydroxide nanomaterials were obtained by co-precipitation of transition metal salt solution and precipitant solution; (2) The transition metal hydroxide nanomaterials are dispersed in an organic solvent and sprayed onto a conductive substrate to obtain a transition metal hydroxide nanoelectrocatalyst.
3. The method according to claim 2, wherein, The conditions for coprecipitation include: a coprecipitation temperature of 50-90℃, preferably 60-85℃; and a coprecipitation time of 5-30 min, preferably 10-15 min.
4. The method according to claim 2, wherein, The transition metal salt includes nickel salts and non-nickel transition metal salts; the non-nickel transition metal salts are selected from at least one of vanadium salts, manganese salts, and copper salts. Preferably, the total mass concentration of the transition metal salt in the transition metal salt solution is 5-50 g / L, and more preferably 10-30 g / L.
5. The method according to claim 4, wherein, The nickel salt is selected from at least one of nickel nitrate, nickel chloride, and nickel sulfate; Preferably, the non-nickel transition metal salt is selected from at least one of vanadium chloride, vanadium nitrate, vanadium oxysulfate, vanadium oxalate, manganese chloride, manganese sulfate, manganese nitrate, copper chloride, copper sulfate, and copper nitrate. Preferably, the mass ratio of the nickel salt to the non-nickel transition metal salt is 4-30:1, more preferably 8-15:
1.
6. The method according to claim 2, wherein, The molar ratio of the transition metal salt in the transition metal salt solution to the precipitant in the precipitant solution is 1:1-4, preferably 1:1.2-2; Preferably, the mass concentration of the precipitant in the precipitant solution is 5-50 g / L, more preferably 14-30 g / L; Preferably, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, potassium bicarbonate, urea, and ammonia.
7. The method according to claim 2, wherein, The conductive substrate is selected from at least one of carbon cloth, carbon paper, nickel foam, nickel sheet, nickel mesh, copper foam, copper sheet, copper mesh, titanium sheet, titanium mesh, stainless steel sheet, stainless steel mesh, ITO conductive glass, and FTO conductive glass.
8. The method according to claim 1, wherein, The cathode catalyst is selected from at least one of platinum, gold, silver, ruthenium, iridium, palladium, copper, and rhodium; Preferably, the cycloalcohol is selected from at least one of cyclobutanol, cyclopentanol, and cyclohexanol; Preferably, the mass concentration of the cyclic alcohol in the electrolyte solution containing cyclic alcohols and / or cyclic ketones is 10-50 g / L, more preferably 30-40 g / L; Preferably, the cyclic ketone is selected from at least one of cyclobutanone, cyclopentanone, and cyclohexanone; Preferably, the mass concentration of the cyclic ketone in the electrolyte solution containing cyclic alcohols and / or cyclic ketones is 10-50 g / L, more preferably 30-40 g / L.
9. The method according to claim 1, wherein, The electrolyte concentration in the electrolyte solution containing cyclic alcohols and / or cyclic ketones is 10-100 g / L, preferably 25-50 g / L; Preferably, the electrolyte is selected from at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide, and cesium hydroxide.
10. The method according to claim 1, wherein, The conditions for the electrocatalytic oxidation include: an electrocatalytic voltage of 0.1-3V, preferably 0.5-1.5V, and an electrocatalytic time of 1-24 hours, preferably 1-10 hours; Preferably, the dicarboxylic acid is selected from at least one of succinic acid, glutaric acid, adipic acid, and the corresponding lithium, sodium, and potassium salts of the three acids.